On the Meaning of Water in Ballads - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2015)
The article departs from the point of ballads as (mostly) pieces of folklore of non-Lithuanian origin taking root and existing in the Lithuanian environment. The ballad Nenustiko broliukui ženybos [‘The Unhappily Married Brother’] (and the song type Augo sode klevelis [‘A Maple Tree Was Growing in the Yard’]), as well as a number of other ballads including the motive of drowning, gravitate towards the topic and thematic of water. The predominance of the water image suggests its symbolic meaning. Thus, the family ballad in question not simply relates of a cruel action – it creates a peculiar “family myth”. The notion of water as a primeval substance points to its cleansing and renewing function. Instead of drowning, the semantic shift is projected towards revival, associated with washing away of the wife’s inadequacy, and finally resulting in caring for her. The Lithuanian ballad is compared to the Belorussian and Ukrainian ballads containing distinct images of the star and of the middle of the sea. Special attention is paid to a couple of texts in which an opposition between the old wife (maiden) and the new wife (maiden) may be spotted. According to Claude Lévi-Strauss, replacement of some oppositions with others is a characteristic of the mythical thinking. The action of the ballad (floating of the wife out to the middle of the sea, and subsequent plea of the husband pulling back and asking her to return) is remotely paralleled in the article with the ritual death and resurrection. However, such parallel does not suggest any specific ritual having allegedly existed in the family customs and perishing afterwards. Although (ritual) death and (ritual) revival are best reflected in rituals (therefore ritual analysis is especially useful here), they can manifest elsewhere too. An assumption is made of this being an archetype, repeatedly emerging on various levels, from the highest to the lowest ones. Examination of the marital relationship in the light of the archetype of birth – death – resurrection considerably broadens the scope of the ballad’s meanings. The archetype suggests its different interpretation.